The supplementation of clove oil Syzygium aromaticum in the diet to improve the growth performance of common carp Cyprinus carpio Linnaeus 1758 - Tira Silvianti; Dedi Jusadi; Sri Nuryati (Jurnal Iktiologi Indonesia, 2016)
The aim of this research was to determine the effect of the diet supplemented with clove oil Syzygium aromaticum on the growth performance of common carp, Cyprinus carpio. The experiment was carried out from February to April 2015 at the Laboratory Production, Department of Aquaculture, Faculty of Fisheries and Marine Sciences, Bogor Agricultural University. Common carp, strain Majalaya with an initial body weight of 3.90±1.08 g were reared in the 50x40x35 cm3 aquaria (150 L volume) at density of 25 fish per aquaria. During the rearing period, fish were fed on the diet contained with clove oil with a dose of 0, 5, 10, 15, or 100 mg 100 g-1 diet with three replications. The experiment for growth performance was conducted for 56 days and followed by digestibility test for 10 days. The fish were fed three times a day at 08:00, 12:00 and 16:00 hours. The results showed that the growth performances of fish were affected by clove oil supplementation. Fish fed on the diet supplemented with clove oil at a dose of 100 mg 100 g-1 diet significantly had the best growth performance and health status, including blood profile and the intestinal villus length. Abstrak Penelitian ini dilakukan dengan tujuan mengevaluasi penambahan minyak cengkeh Syzygium aromaticum dalam pakan untuk meningkatkan kinerja pertumbuhan ikan mas Cyprinus carpio. Penelitian dilakukan pada bulan Februari hingga bulan April 2015, di Laboratorium Produksi, Kolam Percobaan Departemen Budidaya Perairan, Fakultas Perikanan dan Ilmu Kelautan, Institut Pertanian Bogor. Ikan uji yang digunakan adalah mas dari varietas Majalaya yang berbobot 3,90 ±1,08 g. Ikan ditebar pada akuarium berukuran 50x40x35 cm3 (volume 150 L) dengan kepadatan 25 ekor ikan setiap akuarium. Selama masa pemeliharaan, ikan diberi pakan yang mengandung minyak cengkeh dengan dosis 0, 5, 10, 15, atau 100 mg 100 g-1 pakan dengan masing-masing tiga ulangan. Uji pertumbuhan dilakukan selama 56 hari, dilanjutkan dengan uji kecernaan selama 10 hari. Ikan diberi pakan tiga kali dalam sehari, yaitu pukul 08.00, 12.00, dan 16.00. Ha-sil penelitian menunjukkan bahwa kinerja pertumbuhan ikan mas dipengaruhi oleh penambahan minyak cengkeh. Ikan yang diberi pakan dengan penambahan minyak cengkeh pada dosis 100 mg 100 g-1 pakan secara signifikan memiliki kinerja pertumbuhan dan status kesehatan terbaik, termasuk profil gambaran darah dan tinggi vili usus.